Pengembangan Perangkat Pembelajaran Berbasis Pendekatan Saintifik Menggunakan E-Modul Untuk Meningkatkan Kemampuan Koneksi Matematis Peserta Didik Kelas XI SMA - Hamidah, Hamidah; Asmar, Ali; Musdi, Edwin; Permana, Dony (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2023)
This study adapts the Plomp development model by including the stages of preliminary research, prototyping, and evaluation. The tools developed are in the form of lesson plans and electronic modules based on a scientific approach for class XI high school. The tools used are confirmation sheets, observation sheets, questionnaires, interviews and tests. The value of the validity of the lesson plan is 3.5 with a very valid category and the electronic module is 3.28 with a valid category. The practical level of students in the electronics module is 88.39 in the very practical category and according to the educators, it reaches 97.91% for the lesson plan and 89.00% for the electronic boiler module in the very comfortable type. Learning tools based on a scientific approach using e-modules in the form of lesson plans and e-modules are very effective types with an efficiency level of 83.78%. It can be concluded that the scientific approach developed on learning tools using electronic modules on polynomial material is useful, practical and effective in improving the mathematical connection skills of class XI middle school students